2015
DOI: 10.22610/jebs.v7i1(j).558
|View full text |Cite
|
Sign up to set email alerts
|

In competency Aspects of Microfinance Industry: Via SFA approach

Abstract: Microfinance is a well known terminology used for microcredit and financial services for financially deprived community. Through informal, semi-formal and formal ways different institutions has been providing these services. Expenditure of the industry is considered to be high because of its inherent structure, dealing with small loans and having high risk of recovery. Therefore, expected inefficiency is greater than its profit. There are several factors and reason. Through this study, we analyzed few factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…Results obtained in this study are generally in line with the previous research, for instance [10,16,25,26,28,36,68]. The age of the PO has a positive and statistically significant impact on their super-efficiency in two out of the three estimated specifications.…”
Section: Plos Onesupporting
confidence: 92%
See 3 more Smart Citations
“…Results obtained in this study are generally in line with the previous research, for instance [10,16,25,26,28,36,68]. The age of the PO has a positive and statistically significant impact on their super-efficiency in two out of the three estimated specifications.…”
Section: Plos Onesupporting
confidence: 92%
“…Similarly, the efficiency of the POs is also positively and significantly affected by the personnel. Recent empirical research, such as Riaz and Gopal [36], has generally reported similar findings concerning the performance determinants of Pakistan based MFIs.…”
Section: Plos Onementioning
confidence: 58%
See 2 more Smart Citations
“…Simulate values of the parameters. The coefficients α 0 , α 1 , β 0 , and β 1 were generated from uniformly distributed random numbers on the interval [5,10], the standard deviations of inefficiency terms σ w1 and σ w2 were generated from uniform random numbers on the interval [2,3], and the standard deviations of noise terms σ v1 and σ v2 were simulated from uniform random numbers on the interval [0.5, 1]. The dependence between v 1 and w 1 , v 2 and w 2 , and ε 1i and ε 2i were modeled by Gaussian copulas, where the copula parameters ρ 1 , ρ 2 , and ρ 12 were simulated from uniform random numbers on the interval [0.7, 0.95].…”
Section: Comparative Study Of Two Copula-based Simultaneous Sfmsmentioning
confidence: 99%